Small Questions: College Questioning - Building Effective Classroom Questioning - Xu, Xinle (Journal of Education and Educational Technologies, 2023)
One theme is "national rejuvenation". Since the 18th National Congress of the Communist Party of China, national rejuvenation has become the theme of the times, and the Chinese Dream has become the greatest dream since modern times. Liugong Island witnessed the complete destruction of the thousand year dream of the Chinese Empire, and was the starting point of the Chinese dream of the great rejuvenation of the Chinese nation. The typical events marked by the Tianfu Mountain Uprising, as well as the typical figures represented by the Ten Warriors and Nurses of Mashi Mountain, have become powerful footnotes for our party to lead the people in striving for national independence. The socialist construction in Weihai, especially the development and changes since the reform and opening up, have revealed the bright prospects of national rejuvenation with a small perspective. The education base takes "national rejuvenation" as the theme, commanding all teaching sections and points.